Reconstruction of the severely atrophic edentulous maxillae with calvarial bone grafts - Mertens, Christian; Freier, Kolja; Engel, Michael; Krisam, Johannes; Hoffmann, Jürgen; Freudlsperger, Christian (Clinical oral implants research, 2017)
Objectives Treatment of the severely atrophic maxilla with dental implants is challenging due to the insufficient horizontal and vertical bone volume and centripetal resorption pattern of the maxilla. Bone-augmentation procedures are often necessary prior to implant placement. The objective of this study was to assess the suitability of using calvarial bone grafts to enable implant placement in severely atrophic maxillae. Material and Methods Seventeen patients with severe atrophic edentulous maxillae were reconstructed with autogenous calvarial bone grafts. After a 4-month healing period, the patients received a total of 134 dental implants, which were left to heal in submerged positions for 3 months before prosthetic rehabilitation was performed. Patients were followed clinically and radiographically for an average observation period of 53.94 months. Results At the intraoral recipient sites, two infections developed, causing partial loss of the respective bone grafts. Implant placement, however, was possible at all sites. No donor-site complications occurred. Two of 134 implants were lost in two patients prior to prosthetic loading. The implant survival rate was 98.51%. The implant success rate was 87.6%, and a mean marginal bone loss of 0.62 mm (SD 0.77 mm) was documented. Conclusions Patients with severe bone atrophy of the edentulous maxilla can be successfully reconstructed with calvarial bone grafts and dental implants and show a stable clinical and radiographic situation after a mean observation period of 53 months.
First published: 19 May 2016
Gesehen am 27.09.2018